Mefloquine treatment of acute falciparum malaria: a prospective study of non-serious adverse effects in 3673 patients. - ter Kuile, F; Nosten, F; Luxemburger, C; Kyle, D; Teja-Isavatharm, P; Phaipun, L; Price, R; Chongsuphajaisiddhi, T; White, N (1995)
Between 1990 and 1994, a series of prospective studies were conducted to optimize the treatment of multidrug-resistant falciparum malaria on the borders of Thailand. The tolerance of various treatment regimens containing either mefloquine 15 mg/kg (M15) or 25 mg/kg (M25) was evaluated in 3673 patients aged between 6 months and 88 years. Early vomiting (within 1 hour) is an important determinant of treatment outcome in these areas, despite re-administration of the dose. Overall, 7 % of the patients vomited within an hour. Significant risk factors were age < or = 6 years (relative risk (RR), 3.9) or > or 50 years (RR, 2.7), the higher mefloquine dose (M25) (RRm 2.7), vomiting < 24 hours before enrolment (RR, 2.5), axillary temperature > 38.0 degrees C (RR, 1.6), and parasitaemia > 10,000/microliter (RR, 1.3). In children < or = 2 years, 30% vomited with M25, and 13% did not tolerate a repeat dose. Vomiting was reduced 40% by splitting the higher dose (RR, 0.6; 95% CI, 0.4-0.8), and 50% by giving mefloquine on the second day in combination with artesunate (RR, 0.5; CI, 0.3-0.9). Anorexia, nausea, vomiting, dizziness, and sleeping disorders were 1.1-1.4 times more frequent with M25 than M15 in the three days following treatment, but were similar in the single or split-dose M25 groups, despite twofold higher mefloquine concentrations obtained with the latter. There was no evidence that diarrhoea, headache, and abdominal pain were associated with mefloquine use. High-dose mefloquine is well tolerated but should be given as a split dose.